The evaluation of the attitudes of psychology students and grads towards the psychiatric disorders and dependence - Yıldız, Nejla; Mortan Sevi, Oya; Soykal, İlkay; Odabaşıoğlu, Gürkan; Genç, Yasin (Journal of Dependence, 2014)
Objective: The aim of this study to evaluate and compare the attitudes of 3rd/4th grade of psychology students and psychology grads/clinical psychology graduate students towards the psychiatric disorders and alcohol and substance dependence.Method: The sample is consisted of 46 interns who applied to Surp Pırgic Armenian Hospital Psychiatry Clinic between the ages of 21-30. The participants were assessed using Stigmatization toward Alcohol Dependence Questionnaire, Stigmatization toward Substance Dependence Questionnaire, Beliefs toward Mental Illness Scale, and Self-Stigma of Seeking Psychological Help Scale. The scales scores of two groups were compared using Independent Sample T Test.Results: There is not any significant difference in attitudes toward psychiatric diseases and addictive disorders between psychology students and grads (p>0.05). However, both groups have above average scores in stigmatization toward alcohol and substance dependence; below-average scores in stigmatization toward psychiatric disease and selfstigma of seeking psychological help.Conclusion: Results shows that psychology and clinical master programs is needed to be included both teorical and pratical education programs to change the attitudes and beliefs of students toward dependence.
Keywords: Stigmatization; attitude; alcohol and substance dependence; psychiatric disorders; psychology students and grads